Protective effect of fungal extracellular vesicles against murine candidiasis. (22nd July 2020) - Vargas, Gabriele; Honorato, Leandro; Guimarães, Allan Jefferson; Rodrigues, Marcio L.; Reis, Flavia C. G.; Vale, André M.; Ray, Anjana; Nosanchuk, Joshua Daniel; Nimrichter, Leonardo
Abstract: Extracellular vesicles (EVs) are lipid bilayered compartments released by virtually all living cells, including fungi. Among the diverse molecules carried by fungal EVs, a number of immunogens, virulence factors and regulators have been characterised. Within EVs, these components could potentially impact disease outcomes by interacting with the host. From this perspective, we previously demonstrated that EVs from Candida albicans could be taken up by and activate macrophages and dendritic cells to produce cytokines and express costimulatory molecules. Moreover, pre‐treatment of Galleria mellonella larvae with fungal EVs protected the insects against a subsequent lethal infection with C. albicans yeasts. These data indicate that C. albicans EVs are multi‐antigenic compartments that activate the innate immune system and could be exploited as vaccine formulations. Here, we investigated whether immunisation with C. albicans EVs induces a protective effect against murine candidiasis in immunosuppressed mice. Total and fungal antigen‐specific serum IgG antibodies increased by 21 days after immunisation, confirming the efficacy of the protocol. Vaccination decreased fungal burden in the liver, spleen and kidney of mice challenged with C. albicans . Splenic levels of cytokines indicated a lower inflammatory response in mice immunised with EVs when compared with EVs + Freund's adjuvant (ADJ). Higher levels of IL‐12p70, TNFα and IFNγ were detected in mice vaccinated with EVs + ADJ, while IL‐12p70, TGFβ, IL‐4 and IL‐10 were increased when no adjuvants were added. Full protection of lethally challenged mice was observed when EVs were administered, regardless the presence of adjuvant. Physical properties of the EVs were also investigated and EVs produced by C. albicans were relatively stable after storage at 4, −20 or −80°C, keeping their ability to activate dendritic cells and to protect G. mellonella against a lethal candidiasis. Our data suggest that fungal EVs could be a safe source of antigens to be exploited in vaccine formulations.